HUBUNGAN TINGKAT PENGETAHUAN TENTANG KANKER CERVIKS DENGAN PERILAKU SKRINING KANKER CERVIKS PADA IBU PASANGAN USIA SUBUR ( PUS ) DI WILAYAH KELURAHAN BUMIJO, JETIS, KOTA YOGYAKARTA - Budi Punjastuti; Berlina Putrianti; Laily Mualifah (LPPM Politeknik Kesehatan Karya Husada Yogyakarta, 2014)
In Indonesia from 13 pathology laboratories during the period of 1988-1991showed that cervical cancer took the first place of 10 major diseases in women (28.66%).Based on data from the Health Research in 2013,the highest prevalence of cancer inIndonesia is located in Yogyakarta at 0.41% or 4.1 of the 1000 population. In Indonesia,every day at least 20 deaths occurred due to cervical cancer. Measures to reduce deathsfrom cervical cancer continue encouraged one of them to do the screening. In thesubdistrict of Jetis Bumijo, Yogyakarta city is known that most couples of childbearingage who are located in the working area of the village health center Bumijo which is about1,149 pairs. Various methods are used in fertile couples to understand about cervicalcancer and screening in couples of childbearing age is. The purpose of this research is toidentify the rate of cervical cancer on PUS mother (Pasangan Usia Subur).Identifying cervical cancer screening behavior in mothers of , Knowing thecharacteristics of respondents based on age, educational status, and employment status.The benefits of scientific research are proving scientifically the correlation betweencervical cancer knowledge and behaviors of women in cervical cancer screening.Thisresearch is used as an input in the design of programs thatrelated to efforts to improve thecoverage of early detection of cervical cancer and overcoming obstacles - obstacles in theimplementation of early detection of cervical cancer.Research hypothesis is :There is a relationship between the level of knowledgeabout cervical cancer to cervical cancer screening behaviors in women coupleschildbearing age (PUS).This research is an observational analytic research with implementation form ofsurvey. Research design time approach Cross sectional. The research location is in thesubdistrict Jetis Bumijo, Yogyakarta city.Sampling was done by Cluster Sample RandomSampling.The result of the research of the level of knowledge about cervical cancer from300 respondents are: the highest knowledge was 23 people (7.67%),the mediumknowledge was 241 (80.33%), and the low knowledge was 36(12%).Cervical cancerscreening behaviors of 300 respondents was : that is notconducting amounted to 179people (59.67%) and 121 people who did (40.33%). The statistical test that used is theProduct Moment correlation, for analyzing all the variables studied and determinewhether there is a significant relationship at the confidence level ( = 0.05) that the Pvalue equal 0.013 <0.05 (α = 5%) which means there is a significant relationship betweenthe level of knowledge about cervical cancer with cervical cancer screening behaviors inMother of fertile couples (PUS).ConclusionThere is a relationship between the level of knowledge about cervical cancerwith cervical cancer screening behaviors with a p-value of 0.013,where the levels ofknowledge about cervical cancer are increasingly growing high, then more and more highwillingness to undertake cervical cancer screening.